Sleep and stress hormone responses to training and competition in elite female athletes - O`Donnell, S.; Bird, S.; Jacobson, G.; Driller, M. (European Journal of Sport Science, 2018)
Stress hormone and sleep differences in a competition versus training setting are yet to be evaluated in elite female team-sport athletes. The aim of the current study was to evaluate salivary cortisol and perceptual stress markers during competition and training and to determine the subsequent effects on sleep indices in elite female athletes. Ten elite female netball athletes (mean ± SD; age: 23 ± 6 years) had their sleep monitored on three occasions; following one netball competition match (MATCH), one netball match simulation session (TRAIN), and one rest day (CONTROL). Perceived stress values and salivary cortisol were collected immediately pre- (17:15 pm) and post-session (19:30 pm), and at 22:00 pm. Sleep monitoring was performed using wrist actigraphy assessing total time in bed, total sleep time (TST), efficiency (SE%), latency, sleep onset time and wake time. Cortisol levels were significantly higher (p < .01) immediately post MATCH compared with TRAIN and CONTROL (mean ± SD; 0.700 ± 0.165, 0.178 ± 0.127 and 0.157 ± 0.178 µg/dL, respectively) and at 22:00 pm (0.155 ± 0.062, 0.077 ± 0.063, and 0.089 ± 0.083 µg/dL, respectively). There was a significant reduction in TST (-118 ± 112 min, p < .01) and SE (-7.7 ± 8.5%, p < .05) following MATCH vs. TRAIN. Salivary cortisol levels were significantly higher, and sleep quantity and quality were significantly reduced, following competition when compared to training and rest days.